The default risk, enhancement and credit spread: evidence from China - Tang, Meiyazhu (2023)
In the present research, the fiscal data of the bond issuer from Shanghai stock exchange is investigated with an aim of investigating the determinative factors for the credit spread. As expected, the regression results suggested that the credit spread is positively related to the leverage of the bond issuer, capital market liquidity, and the performance of the stock market, while it is negative related to the bond issuer’s profitability. Moreover, the size of the issuer is not related to the credit spread. This may be because all issuers in the Chinese debt market are companies with larger total assets. The advantage of large companies is less evident in the bond market of China. The regression results also indicate that the impact of bond issuers' rating rankings on credit spreads has less statistical significance. This may be because all rating rankings in the Chinese bond market are provided by local rating agencies. Their rating results appear to be less credible than those of rating agencies with international reputations.